International EIA Guidelines and the Nile Basin Countries EIA Experience - El Gohary, Rasha (European Scientific Journal, ESJ, 2016)
The environmental impact assessment (EIA) was first required by the U.S. National Environmental Policy Act, which require environmental impact assessment of all major development projects to determine their potential for adverse effects on the environment. The environmental outlook for the Nile basin remains quite hazy. In the future there will be new environmental challenge stemming from population growth, increasing demands on agriculture, and climate change. This will put a huge burden on the environment. This research initiated to compare the international EIA guidelines in order to enhance the Nile Basin Countries experience to improve its practice in managing the environmental resources. This is due to the fact that Nile Basin Countries experiences face many challenges such as lack of capacity, data, proper guidelines, enforcement, and most importantly awareness of the environment protection sector or its effectiveness. Moreover; it requires reviewing and tools improvements to produce effective environmental management of development and engineering projects. Therefore, provision of detailed guidelines for EIA can help to improve the practice in the management of environmental resources. This paper reviews the EIA legislation in the Nile Basin Countries in comparison with international legislation and guidelines with emphasis on the EIA practice. The paper also intends to present selected international EIA guidelines in a comparative form and this is expected to raise awareness, professional experience of EIA issues, enhance EIA carrying capacity, and lead, ultimately, to improvements in available EIA legislations and guidelines and increase compatibility among them.